Progress(es), theories and practices : proceedings of the 3rd International Multidisciplinary Congress on Proportion Harmonies Identities (PHI 2017), October 4-7, 2017, Bari, Italy /: proceedings of the 3rd International Multidisciplinary Congress on Proportion Harmonies Identities (PHI 2017), October 4-7, 2017, Bari, Italy. (2017) - Unknown
No abstract available